The Influence of Identity Status and Parental Support toward Career Maturity in Final-Year Undergraduate Students - Nur’afiah, Yuni; Hernawati, Neti (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2024)
Considering future alternatives such as determining career plans is a fairly complex challenge for teenagers. Although college graduates have a longer learning experience than other education levels, there is still open unemployment in college graduates. This is due to students' low career maturity, whichh is influenced by their identity status and the support of their parents. This study analyzes the influence of adolescent characteristics, family characteristics, identity status, and parental support on career maturity. A total of 100 respondents included in this study consisted of 48 male and 52 female final-level undergraduate students selected by proportional random sampling technique. Data were collected through questionnaires, then the data were analyzed using descriptive and inferencing analysis. The results showed that the identity status of achievement and father autonomy support had a significant positive effect on career maturity. In contrast, diffusion identity status and moratorium hurt career maturity. There were no significant differences between the career maturity of male and female respondents. Therefore, colleges and universities should implement comprehensive career guidance programs involving parents to ensure consistent and effective support.